DASYCLADALES (GREEN ALGAE) AND SOME BENTHIC FORAMINIFERA FROM THE UPPER CRETACEOUS ILAM FORMATION (LATE CONIACIAN–SATONIAN), SW IRAN (ONSHORE AND OFFSHORE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
New data (onshore, offshore) on the Upper Cretaceous Ilam Formation of southwestern Iran are provided concerning the common presence of dasycladalean green algae (families Triploporellaceae, Polyphysaceae) that have so far been treated mostly in open nomenclature. The assemblage consists of the five taxa Salpingoporella ubaiydhi Radoičić, 1979, Dissocladella ondulata (Raineri, 1922), Trinocladus tripolitanus Raineri, 1922, Clypeina cf. dusanbrstinai Radoičić, 1997, and gen. et sp. indet. The taxa typically prevail in wackestones-packstones but exhibit different distributional patterns. While S. ubaiydhi and T. tripolitanus, rarely associated with D. ondulata, form a characteristic assemblage in a distal infralittoral facies (more diverse assemblage; zone no. 31 of Wynd, 1965), C. cf. dusanbrstinai occurs in a proximal infralittoral facies associated with miliolids among also complex forms (rhapydioninids) (assemblage zone no. 30 of Wynd, 1965). It is concluded that the two assemblage zones refer to different palaeoenvironments, instead of different ages (‘lower’ and ‘upper’). Based on benthic foraminifera, the main part of the Ilam Formation can be ascribed to the Santonian. For the lower part, a late Coniacian age is suggested implied indirectly by the comparably long vertical range of the rotaliid Orbitokathina vonderschmitti Hottinger, 1966 of the studied core. This would be in conformity with the K 150 Arabian Plate K 150 sequence boundary referring to a late Turonian?–early Coniacian hiatus. From a palaeobiogeographic perspective, T. tripolitanus is a cosmopolitan species, S. ubaiydhi is restricted to the area of the former Arabian Plate (subsurface Iraq, Saudi Arabia and Egypt), while C. dusanbrstinai has been recorded only from Serbia (type-locality). In addition to the algae, the stratigraphic discussion includes the occurrence of the benthic foraminifera Reticulinella? kaeveri Cherchi, Radoičić & Schroeder, 1989 and Orbitoides mid-orientalis (Eames & Smout, 1956) in the Ilam Formation.